A new procedure for the cloning, expression and purification of the β-carbonic anhydrase from the pathogenic yeast Malassezia globosa, an anti-dandruff drug target. (1st November 2016) - Del Prete, Sonia; De Luca, Viviana; Vullo, Daniela; Osman, Sameh M.; AlOthman, Zeid; Carginale, Vincenzo; Supuran, Claudiu T.; Capasso, Clemente
Abstract: Malassezia yeasts are almost exclusively the single eukaryotic members of the fungal flora of the skin. Malassezia globosa and Malassezia restricta are found on the skin of practically all humans. Malassezia globosa is highly implicated in the pathogenesis of dandruff and its genome encodes for only one carbonic anhydrases (CAs, EC 4.2.1.1) belonging to the β-class (MgCA). It has been indeed demonstrated that in many pathogenic microorganisms, CAs are essential for their life cycle and their inhibition can lead to growth impairment and defects. In the previous work, the recombinant MgCA was investigated for its inhibition profile with sulfonamides, which in models of dandruff infection were able to protect animals from the fungal infection, allowing us to propose this enzyme as a new antidandruff target. MgCA was cloned as GST-fusion protein, but the yield was rather low and the protein was often found in inclusion bodies. Here, we propose an alternative procedure consisting in cloning the recombinant MgCA as His-Tag fusion protein. This procedure resulted in a good method to express and purify the active recombinant MgCA, and the protein recovery was better with respect to that used for preparing MG-CA (β-CA cloned as GST-fusion protein).